L’adaptation du théâtre de Molière en arabe : L’exemple de la démarche de ‘Uṯmān Jalāl - Ons Trabelsi (Carnets)
It is appropriate here to observe the process of appropriation of Molière's theater and the settlement of a modern tradition through a composite approach mainly based on borrowing processes in the Molière Comedy and forms inherited from the traditional Arab theater in order to answer to an always changing horizon. The Egyptian dramatist 'Uṯmān Jalāl presents an example of appropriation of the French texts which will later be taken up by the Syrian-Egyptian troops formed at the end of the 19th century.